2013
DOI: 10.1515/bejeap-2013-0047
|View full text |Cite
|
Sign up to set email alerts
|

Pass-through of Per Unit and ad Valorem Consumption Taxes: Evidence from Alcoholic Beverages in France

Abstract: Economic theory states that in a market with imperfect competition, per unit consumption taxes should induce a greater increase in prices than ad valorem consumption taxes. This implies that consumers bear a greater share of the tax burden with per unit consumption taxes than that with ad valorem consumption taxes. This article seeks to test this theoretical result empirically using the French market for alcoholic beverages, which is subject to both per unit (excise taxes) and ad valorem (value-added tax, VAT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 25 publications
1
18
0
2
Order By: Relevance
“…Wicksell (1896) demonstrated this result in the case of a monopoly with constant marginal costs, Suits and Musgrave (1953) for all monopolies, Delipalla and Keen (1992) under Cournot oligopoly with conjectural variations and Anderson et al (2001b,a) under Bertrand oligopoly. This result has been empirically confirmed by Delipalla and O'Donnell (2001) and Carbonnier (2011) using respectively the european tabacco market and the French alcohol market.…”
Section: Introductionsupporting
confidence: 52%
See 1 more Smart Citation
“…Wicksell (1896) demonstrated this result in the case of a monopoly with constant marginal costs, Suits and Musgrave (1953) for all monopolies, Delipalla and Keen (1992) under Cournot oligopoly with conjectural variations and Anderson et al (2001b,a) under Bertrand oligopoly. This result has been empirically confirmed by Delipalla and O'Donnell (2001) and Carbonnier (2011) using respectively the european tabacco market and the French alcohol market.…”
Section: Introductionsupporting
confidence: 52%
“…This has been confirmed theoretically by Stern (1987) and Besley (1989) for homogenous products and Anderson et al (2001b,a) for heteregenous products; it has been also empirically confirmed by Besley and Rosen (1999) and Carbonnier (2007Carbonnier ( , 2009Carbonnier ( , 2011.…”
Section: Introductionmentioning
confidence: 58%
“…Therefore, competition in ad valorem tax yields lower tax revenue than competition in unit tax. This result suggests a critical implication that governments are plunged into a prisoner's dilemma when choosing their tax 1 A recent study by Carbonnier (2011) tests this theoretical hypothesis and finds that in the alcoholic beverages market in France, the shifting of prices of per unit excise taxes was significantly larger than the shifting of ad valorem VAT.…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide range of alcohol tax incidence estimates, with some studies showing that alcohol taxes are undershifted onto consumers (i.e., the price passed onto consumers goes up by less than the amount of the tax) and others suggesting that prices increase by as much as four times the amount of the tax (Barzel 1976;Carbonnier 2013;Kenkel 2005;Young and Bielinska-Kwapisz 2002); see Dutkowsky and Sullivan (2014) for a review of this literature. 1 There is also a growing literature on tax salience (Chetty 2009;Chetty, Looney, and Kroft 2009;Finkelstein 2009;Hayashi, Nakamura, and Gamage 2013), but this work still remains sparse relative to the incidence literature.…”
Section: Abstract Alcohol Tax Incidence Saliencementioning
confidence: 99%
“…It is less common in previous work to separately identify the incidence of excise and sales taxes. In regard to the alcohol literature, only Chetty, Looney, andKroft (2009) andCarbonnier (2013) have analyzed how differences between ad valorem and excise (per unit) taxes differentially impact this market. Carbonnier (2013) finds that the change in prices due to excise taxes was significantly larger than that due to value-added taxes in the French market for alcohol.…”
Section: Olsmentioning
confidence: 99%